INFLUENCE OF SOMATIC COMORBIDITY ON THE COURSE OF CORONARY HEART DISEASE - E. B. Akhmedova; B. U. Mardanov; M. N. Mamedov (Российский кардиологический журнал)
Aim. To assess the life quality and clinical-laboratory parameters of the stable coronary heart disease (CHD) patients comorbid with diabetes type 2 (DM) and chronic obstructive pulmonary disease (COPD).Material and methods. Totally, 67 patients included, age 39-69 y.o. All patients were selected to 3 groups: CHD (group 1, n=21, mean age 55,4±6,8 y.o., males/ females 16/5), CHD and DM (group 2, n=21, 58,8±8,9 y.o., M/F 18/6), and CHD and COPD (group 3, n=22, 59,2±5,2 y.o., M/F 16/6). Clinical and anamnestic, as biochemical and hemodynamic parameters were evaluated, and the life quality with EQ-5D score.Results. In the CHD group with or none DM there was high rate of obesity, but in COPD group mean body mass index was lower than 29 kg/m2 . By EQ-5D, life quality decrease in CHD and DM, at most was determined by the units as “dyscomfort”, “everyday activities” and “anxiety/depression”. In CHD patients with comorbid COPD maximum was collected in the points related to “mobility”, “anxiety/ depression”. In the absence of significant dilation of the left ventricle (LV), in the patients of groups 2 and 3 there were relatively low values of ejection fraction (EF) comparing to CHD only patients. Also, in COPD and CHD patients there were signs of the left atrium overload, as the Doppler digns of pulmonary hypertension. Comorbidity of CHD and DM was followed by increased plasma urea and more significant dyslipidemia.Conclusion. Comorbid DM and COPD contribute on the worsening of CHD patients parameters with following decline in life quality, increased plasma urea and more significant dyslipidemia.